2021
DOI: 10.1002/adma.202008234
|View full text |Cite
|
Sign up to set email alerts
|

Tip‐Induced Nano‐Engineering of Strain, Bandgap, and Exciton Funneling in 2D Semiconductors

Abstract: The tunability of the bandgap, absorption and emission energies, photoluminescence (PL) quantum yield, exciton transport, and energy transfer in transition metal dichalcogenide (TMD) monolayers provides a new class of functions for a wide range of ultrathin photonic devices. Recent strain‐engineering approaches have enabled to tune some of these properties, yet dynamic control at the nanoscale with real‐time and ‐space characterizations remains a challenge. Here, a dynamic nano‐mechanical strain‐engineering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 55 publications
1
67
0
Order By: Relevance
“…The ideal nanoscale strain-gradient structure for effective X 0 funnelling and X-conversion exists in nature, i.e., the nanoscale wrinkle in 2D TMDs. Our previous study revealed the exciton funnelling behaviors of the naturally-formed wrinkles in a WSe 2 ML [12]. As experimentally confirmed again in this study, the uniaxial tensile strain is induced in the wrinkle structure with the highest strain at the apex region, which facilitates the exciton funnelling to the lowest bandgap energy region, spatially at the nanoscale.…”
Section: Exciton Dynamics and Trion Conversions In Nanoscale Wrinklessupporting
confidence: 86%
See 1 more Smart Citation
“…The ideal nanoscale strain-gradient structure for effective X 0 funnelling and X-conversion exists in nature, i.e., the nanoscale wrinkle in 2D TMDs. Our previous study revealed the exciton funnelling behaviors of the naturally-formed wrinkles in a WSe 2 ML [12]. As experimentally confirmed again in this study, the uniaxial tensile strain is induced in the wrinkle structure with the highest strain at the apex region, which facilitates the exciton funnelling to the lowest bandgap energy region, spatially at the nanoscale.…”
Section: Exciton Dynamics and Trion Conversions In Nanoscale Wrinklessupporting
confidence: 86%
“…The specific details for the physical mechanism are depicted with a theoretical model in Fig. 5, which was not considered in our recent report [12]. In contrast, the TEPL intensity decreases with distinctly increased linewidth at the wrinkle for a MoS 2 ML compared to the crystal face region, as shown in Fig.…”
Section: Exciton Dynamics and Trion Conversions In Nanoscale Wrinklesmentioning
confidence: 92%
“…with δ, h, λ, and σ being the bubble height, layer thickness, bubble width, and Poisson's ratio of WSe 2 , respectively. 21 With a base width and height of ∼125 nm and ∼11.5 nm, respectively, and with a Poisson's ratio of 0.19, 23 ε t of this bubble is ∼0.75%. This tensile strain leads to a reduction of ∼37.5 meV in the band gap (i.e., ΔE g ≈ −37.5 meV), assuming a linear relation between ΔE g and ε t with a proportionality ratio of ∼−50 meV/%.…”
mentioning
confidence: 93%
“…20 Similarly, the manipulation of local strain fields and heterostructure architectures was used to control exciton localization and emission. 21,22 In this work, we use hyperspectral nanophotoluminescence (nano-PL) to image excitonic emission from WSe 2 (top layer)/MoSe 2 (bottom layer) heterobilayer structures. We observe strong localization of positively charged trions of the WSe 2 layer inside individual heterostructure nanobubbles.…”
mentioning
confidence: 99%
“…Localized potentials can be either deterministically induced, for example, by patterned substrates and helium irradiation, or they build up naturally in the form of defects and disorder ,, or nanobubbles. Bubbles are naturally formed in experiments when depositing the 2D material on a substrate, ,,, similar to the everyday process of air bubbles forming when putting a plastic foil on glass. Bubbles in various monolayers and of different dimensions can also be obtained via bottom-up approaches such as ionic irradiations. , Nanobubbles are able to induce an energy confinement due to the interplay of strain and local screening variations, resulting in a nontrivial circular shape recently observed in experiments. , Besides being extensively studied via optical response, , localized potentials can impact also the transport and associated recombination in different hosting 2D materials ,, and even lead to excitonic funneling for larger potentials. …”
Section: Introductionmentioning
confidence: 99%